Rhyme, Resistance, and Representation: Intersectional Identities in Contemporary Hip-Hop Lyrics - Hutami , Nestiani (Harmonia : Journal of Music and Arts, 2025)
Hip-hop has become a global platform for articulating cultural and political identities, especially for marginalized communities. This study examines how race, gender, class, and place are represented in hip-hop lyrics through rhetorical and linguistic strategies. Utilizing a structured codebook, five tracks from the United States, United Kingdom, and Global South contexts were analyzed using both qualitative and quantitative methods. The analysis revealed that identity markers such as race and class frequently appear alongside rhetorical devices like metaphor, intertextuality, and naming, which enhance political commentary. Linguistic forms such as African American Vernacular English, code-switching, and alliteration were also found to reinforce cultural authenticity and resistance. These findings demonstrate that hip-hop lyrics function as more than artistic expression; they are discursive tools that challenge dominant ideologies and assert marginalized experiences. This study contributes a replicable analytical framework for examining identity in popular music and highlights the role of hip-hop as a global cultural force for social critique and community formation.